The impact of botfly parasitism on the health of the gracile mouse opossum (Gracilinanus agilis) - Zangrandi, Priscilla Lora; Mendonca, Andre Faria; Cruz-Neto, Ariovaldo Pereira [UNESP]; Boonstra, Rudy; Vieira, Emerson M. (Cambridge Univ Press, 2019)
Fragmented habitats generally harbour small populations that are potentially more prone to local extinctions caused by biotic factors such as parasites. We evaluated the effects of botflies (Cuterebra apicalis) on naturally fragmented populations of the gracile mouse opossum (Gracilinanus agilis). We examined how sex, food supplementation experiment, season and daily climatic variables affected body condition and haemoglobin concentration in animals that were parasitized or not by botflies. Although parasitism did not affect body condition, haemoglobin concentrations were lower in parasitized animals. Among the non-parasitized individuals, haemoglobin concentration increased with the increase of maximum temperature and the decrease of relative humidity, a climatic pattern found at the peak of the dry season. However, among parasitized animals, the opposite relationship between haemoglobin concentration and relative humidity occurred, as a consequence of parasite-induced anaemia interacting with dehydration as an additional stressor. We conclude that it is critical to assess how climate affects animal health (through blood parameters) to understand the population consequences of parasitism on the survival of individuals and hence of small population viability.
Keywords: Body condition; climatic variables; Cuterebra apicalis; cuterebrid; Didelphidae; haematology; myiasis